ANALISIS MAKNA TUTURAN DALAM UPACARA NGELEGI BESI MERSIK (TUMBUK LADA) DALAM MASYARAKAT KARO DI DESA NAMO SERIT KABUPATEN DELI SERDANG KAJIAN: SEMANTIK - Enda Rejeki Tarigan (Kampus Akademik Publiser, 2025)
The Ngelegi Besi Mersik ceremony is an important tradition in the Karo community, particularly in Namo Serit Village, Deli Serdang Regency. This ceremony aims to provide spiritual strength to the Tumbuk Lada knife through a blessing from the kalimbubu (family elders). This study analyzes the meaning of the speech acts in the ceremony using a semantic approach. Data were collected through literature study and observation of relevant sources. The analysis results indicate that the speech acts in this ceremony carry cultural values and philosophies of the Karo people, reflected in the choice of words, expressions, and symbolism used. A deep understanding of the meaning of these speech acts can enrich knowledge about oral traditions and the culture of the Karo community.